New Directions in Teacher Education in East Africa - Kajubi, W. Senteza (International Review of Education, 1971)
The three countries of Kenya, Tanzania and Uganda, of 650,000 square miles and an estimated population million, form a compact geographical and quasi-political East African Community. They have much in common: Lake Victoria; they have a common historical and political having been until recently under British administration. common market and customs union, and an inter-state running such services as railways, harbours, posts and telecommunications, aviation, research, and (until June 1970) a federal university. share the same problems relating to their economic and social This paper is concerned with the problems involved in improvement of education in these countries, with particular the education of teachers.